Association between Frailty and Dialysis Symptom Index among Chronic Hemodialysis Patients in Indonesia - Hosea Glory; Jeremia Immanuel Siregar (Medicinus, 2026)
Background: Chronic kidney disease (CKD) is one of the causes of global death with 79% of them being stage G3-G5, so it is not uncommon for people to require hemodialysis. However, on the other hand, hemodialysis patients have a high risk of experiencing side effects, especially frailty. It is also known that frailty can worsen the side effects of hemodialysis, even death. Therefore, this study aimed to investigate the relationship between frailty and the dialysis symptom index in chronic hemodialysis patients.   Methods: This research uses a cross-sectional method with an unpaired numerical comparative analytical study design. Data was obtained using the Dialysis Symptom Index questionnaire and the RAPUH questionnaire. This research targets patients undergoing chronic hemodialysis aged 18 years and over. The statistical test for this research uses the T Test or Mann-Whitney Test method.   Result: There were 35 patients (24.8%) undergoing hemodialysis who experienced frailty and 106 patients (75.2%) who did not experience frailty. Significant symptoms in frailty patients undergoing hemodialysis are lack of appetite (p < 0.001), shortness of breath (p = 0,039), feeling lightheaded or dizzy (p = 0,022), feeling tired or lacking energy (p < 0.001), dry mouth (p = 0,004), bone or joint pain (p = 0,001), difficulty sleeping (p = 0,014), waking up easily (p = 0,007), decreased sexual desire (p < 0.001), and difficulty becoming aroused sexually (p < 0.001).   Conclusions: In this study, there was a significant relationship between frailty and the side effects of hemodialysis. The most common symptoms are feeling tired or lacking energy, decreased sexual desire, difficulty becoming sexually aroused, waking up easily, muscle cramps, and difficulty sleeping.